Make : Electronics, 3rd Edition - Platt, Charles (Make (Maker Media, Inc.), 2021)
Make: Electronics explores the properties and applications of discrete components that are the fundamental building blocks of circuit design. Understanding resistors, capacitors, transistors, inductors, diodes, and integrated circuit chips is essential even when using microcontrollers. Make: Electronics teaches the fundamentals and also provides advice on the tools and supplies that are necessary. Component kits are available, specifically developed for the third edition.